Methodological considerations and cognitive factors underlying sustained attention - Shalev, N (2017)
The active, ongoing maintenance of an adequate level of performance over time on task is an essential cognitive faculty, and has been described in multiple frameworks since the earliest days of cognitive research. Theoretical accounts of performance maintenance focused on the timely fluctuations of attention components, using the partially overlapping constructs of sustained attention, arousal, vigilance and alertness. In this thesis, particular attention is given to sustained attention, arguably the most useful and frequently used construct in a clinical context. Chapter 1 provides an introductory overview of the literature, focusing on the theories and paradigms available to assess sustained attention and other closely related constructs. Chapter 2 introduces a new task for assessing sustained attention, based on a variation of the Continuous Performance Task (CPT), and discusses the contribution of various task factors to performance patterns. In Chapter 3, the newly established paradigm is used to assess sustained attention among stroke survivors and the healthy ageing, and relate task-performance to subjective reports of daily lapses in attention. A detailed discussion is devoted to identifying the task indices that best represent sustained attention capacity, favouring measures incorporating the notion of change in performance over time. Chapter 4 applies the same approach of estimating change in performance over time to studying sustained attention among children with genetic developmental disorders. Chapters 5 and 6 show how performance in a CPT is influenced by the pace at which stimuli are presented in the task. It is argued that individuals are sensitive to varying levels of temporal regularities; consequently, when measuring sustained attention, researchers must account for the rhythmic pattern that the CPT may introduce. Chapter 7 will present an intervention study combining brain stimulation and a spatially-lateralised CPT paradigm, demonstrating changes in components of Selective Attention as defined by a computational model. The thesis is concluded in Chapter 8, which discusses the contributions of the experimental findings to the understanding of sustained attention and associated experimental methods. The thesis proposes a clear mapping of sustained attention with relation to other closely related constructs, and attempts to provide useful tools for improving clinical assessment.